2014
DOI: 10.1016/j.scitotenv.2014.03.138
|View full text |Cite
|
Sign up to set email alerts
|

Effect of wind speed and relative humidity on atmospheric dust concentrations in semi-arid climates

Abstract: Atmospheric particulate have deleterious impacts on human health. Predicting dust and aerosol emission and transport would be helpful to reduce harmful impacts but, despite numerous studies, prediction of dust events and contaminant transport in dust remains challenging. In this work, we show that relative humidity and wind speed are both determinants in atmospheric dust concentration. Observations of atmospheric dust concentrations in Green Valley, AZ, USA, and Juárez, Chihuahua, México, show that PM10 concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
109
3
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 254 publications
(123 citation statements)
references
References 29 publications
7
109
3
4
Order By: Relevance
“…Xu et al (2011) confirmed the deterministic impact of wind speed and wind direction on the concentration of various trace gases at a suburban site between two mega-cities. Csavina et al (2014) examined dust events in two semi-arid sites and then showed a complex, nonlinear dependence of PM 10 (particulate matter with aerodynamic diameters ≤ 10 µm) on wind speed and relative humidity.…”
Section: Y Zheng Et Al: Impact Of Atmospheric Circulations On Aementioning
confidence: 99%
“…Xu et al (2011) confirmed the deterministic impact of wind speed and wind direction on the concentration of various trace gases at a suburban site between two mega-cities. Csavina et al (2014) examined dust events in two semi-arid sites and then showed a complex, nonlinear dependence of PM 10 (particulate matter with aerodynamic diameters ≤ 10 µm) on wind speed and relative humidity.…”
Section: Y Zheng Et Al: Impact Of Atmospheric Circulations On Aementioning
confidence: 99%
“…In arid and semi-arid climates of North America (Arizona, New Mexico, California, Utah, Colorado and Texas), dust storms are commonly observed, particularly during the March-May period [109,110]. Several dust episodes can be observed over the southern USA in March 2014, some of them have been discussed and commented in media and press release of scientific institutions only.…”
Section: Dust Outbreaks Over North Americamentioning
confidence: 99%
“…The high PM 2.5 mass concentration usually appeared with the higher relative humidity, windless and less rainfall weather, authors can found that three highest concentration days during observation period, all related with these meteorological factors. Higher RH was often associated with windless, cloudy, and insufficiently sunny days, which aggravated the accumulation and chemical reaction of pollutants [14].…”
Section: Relationship Between Major Components Of Pm 25 and Meteorolmentioning
confidence: 99%